2019
DOI: 10.2147/tcrm.s224533
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative Results Between “Epi-Off” Conventional and Accelerated Corneal Collagen Crosslinking for Progressive Keratoconus in Pediatric Patients</p>

Abstract: PurposeThe aim of our study was to evaluate the efficacy and safety of epi-off conventional and accelerated corneal collagen cross-linking in the treatment of progressive keratoconus in pediatric patients up to 4 years after treatment.Patients and methodsConventional (standard) CXL epi-off technique was performed in 37 eyes (S-CXL group) and accelerated CXL in 27 eyes (A-CXL group). Refraction, keratometry, cylindrical equivalent, spherical equivalent, slit lamp examination, pachymetry, corneal tomography, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Meta-analysis about the comparison of epithelium-off versus transepithelial CXL in adult or mixed-age (both adult and children) patients suggests SCXL and TCXL might provide a comparable effect on visual, refractive, pachymetric and endothelial outcomes post-surgery, 11 however in pediatric population such an analysis is still unavailable. Given the publications of new trials and comparative observations for CXL of different protocols in long-term follow-ups, [12][13][14][15][16] an update of summery is necessary. Hence, we conducted a meta-analysis to compare the e cacy of SCXL with ACXL, TCXL and A-TCXL in pediatric keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis about the comparison of epithelium-off versus transepithelial CXL in adult or mixed-age (both adult and children) patients suggests SCXL and TCXL might provide a comparable effect on visual, refractive, pachymetric and endothelial outcomes post-surgery, 11 however in pediatric population such an analysis is still unavailable. Given the publications of new trials and comparative observations for CXL of different protocols in long-term follow-ups, [12][13][14][15][16] an update of summery is necessary. Hence, we conducted a meta-analysis to compare the e cacy of SCXL with ACXL, TCXL and A-TCXL in pediatric keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…Although a decrease was present in the mean CA values of the pediatric group patients at the 12th month compared to the preoperative period, the difference was not statistically signi cant (p: 0.345). Similarly, the difference between the postoperative 1st year CA values and the preoperative ones was not found to be signi cant for either procedure in the study by Nicula et al comparing S-CXL and A-CXL treatments [49]. However, postoperative 2nd year CA values were found to be signi cantly lower in the study of Padmanabhan et al where the S-CXL results in pediatric patients were investigated [44].…”
Section: Discussionmentioning
confidence: 91%
“…A study conducted by Nicula et al 11 concluded that after a 4-year follow-up, standard CXL reduced K1 from 47.41 D to 45.36 D (p = 0.004) and K2 from 51.98 D to 50.21 D (p = 0.0078), thus significantly contributing to the stabilization of keratoconus. In the Accelerated CXL protocol with 9 mW/cm 2 UVA irradiation for 10 minutes, there was also a reduction in K1 values, which decreased from 46.97 D to 44.96 D (p = 0.0048), and in K2 values, which decreased from 50.55 D to 48.75 D (p = 0.0287).…”
Section: Discussionmentioning
confidence: 98%
“…We included patients who had at least 0.75 D progressive steepening of the anterior corneal surface associated with progressive steepening of the posterior corneal surface, in two consecutive exams at least 6 months apart. 11,12 The exclusion criteria were patients with a corneal thickness of less than 450 microns, those previously treated (CXL or ring implant) and those who did not complete the minimum follow-up of 6 months. Keratometry measurements were obtained using a WaveLight Topolyzer topographic system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation